Multipotent Effect of Clozapine on Lipopolysaccharide-Induced Acetylcholinesterase, Cyclooxygenase-2,5-Lipoxygenase, and Caspase-3: In Vivo and Molecular Modeling Studies - Minhajul Arfeen; Devendra Kumar Dhaked; Vasudevan Mani (Molecules)
Dual inhibition of cyclooxygenase-2 (COX-2) and lipoxygenase (LOX) is a recognized strategy for enhanced anti-inflammatory effects in small molecules, offering potential therapeutic benefits for individuals at risk of dementia, particularly those with neurodegenerative diseases, common cancers, and diabetes type. Alzheimer’s disease (AD) is the most common cause of dementia, and the inhibition of acetylcholinesterase (AChE) is a key approach in treating AD. Meanwhile, Caspase-3 catalyzes early events in apoptosis, contributing to neurodegeneration and subsequently AD. Structure-based virtual screening of US-FDA-approved molecules from the ZINC15 database identified clozapine (CLOZ) as the dual inhibitor of COX-2 and AChE, with significant binding affinity. Further molecular docking of CLOZ in the active site of LOX and Caspase-3 also showed significant binding potential. Further, the results from molecular docking were validated using molecular dynamics simulation (MDS) studies, confirming the results from molecular docking. The results from MDS showed good binding potential and interactions with key residues. The CLOZ was further assessed using lipopolysaccharide (LPS)-challenged rats treated for thirty days at doses of 5 and 10 mg/kg, p.o. The results demonstrated modulation of COX-2, 5-LOX, AChE, Caspase-3, and MDA in LPS-induced brains. Additionally, the expression level of IL-10 was also measured. Our results showed a significant decrease in the levels of COX-2, 5-LOX, AChE, Caspase-3, and MDA. Our results also showed a significant decrement in the pro-inflammatory markers NF-κB, TNF-α, and IL-6 and an improvement in the levels of anti-inflammatory markers IL-10 and TGF-β1. Overall, the findings indicate that CLOZ has potential for neuroprotective effects against LPS-treated rats and can be explored.